2007
DOI: 10.1021/ja066351g
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Tuning from Normal to Inverted Marcus Region of Intramolecular Electron Transfer in Ferrocene-Based Organic Radicals

Abstract: The solvent dependence of spectroscopic data of two neutral paramagnetic donor-acceptor dyads, based on a polychlorinated triphenylmethyl radical acceptor unit linked through a vinylene pi-bridge to a ferrocene (compound 1) or a nonamethylferrocene donor (compound 2) unit, is described. Both compounds exhibit broad absorptions in the near-IR region, with band maxima appearing around 1000 and 1500 nm for 1 and 2, respectively. These bands correspond to the excitation of a neutral DA ground state to the charge-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 105 publications
6
99
0
Order By: Relevance
“…A paramagnetic and electronically switchable compound that has attracted a great deal of attention during the last decades in the field of molecular electronics and spintronics is the perchlorotriphenylmethyl (PTM) radical (see Figure ), with many derivatives studied in solution,,, crystals,,, under the form of Self‐Assembled Monolayers (SAMs),, or in molecular junctions ,,. These radical systems exhibit a high chemical and thermal stability and present very different electronic, optical, and magnetic properties compared to the corresponding closed‐shell or anionic forms.…”
Section: Introductionmentioning
confidence: 99%
“…A paramagnetic and electronically switchable compound that has attracted a great deal of attention during the last decades in the field of molecular electronics and spintronics is the perchlorotriphenylmethyl (PTM) radical (see Figure ), with many derivatives studied in solution,,, crystals,,, under the form of Self‐Assembled Monolayers (SAMs),, or in molecular junctions ,,. These radical systems exhibit a high chemical and thermal stability and present very different electronic, optical, and magnetic properties compared to the corresponding closed‐shell or anionic forms.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrocene (Fc) and polyazine ruthenium complexes are two commonly used redox species for MV systems because of their well‐defined redox processes and the feasibility of structure modifications. In addition to symmetric structures,2, 7 redox asymmetric systems have also been well studied, as demonstrated by the early works of the groups of Taube,8 Henry,9 Sato,10 Meyer,11 and Long,12 as well as more recent works by Kaim,13 Low,14 Yuan,15 Liu,16 van Koten,17 Veciana,18 Winter,19 and Zhong,20 among others 21. However, studies on the changes of E op by a combined method of structure modification and solvent variation are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Along the same research line we previously reported IET studies based on PTM dyads using ferrocenes as electron donor subunits in solution. [7] Moreover, the bistability phenomenon of one of these dyads in solid state was properly rationalized. [8] Here we focus on the study of the selfassembly of dyad 1 in solution induced by the associated IET process.…”
mentioning
confidence: 99%